Photoacoustic phase angle for noninvasive monitoring of microcirculatory change in human skin: a preliminary investigation - Hui, Ling Chua; Huong, Audrey (Penerbit Universiti Teknologi Malaysia Press, 2022)
Tissue oxygen monitoring systems, such as pulse oximeter, is unreliable in patients with compromised microcirculation. Modern imaging modalities such as Magnetic Resonance Imaging (MRI) offer good diagnostic accuracy at the expense of increased cost and complexity in their operations. This paper studies the use of photoacoustic (PA) phase change as a predictor of skin tissue oxygen levels. We used EPOCH 650 ultrasonic flaw detector with a longitudinal transducer for measurement of PA waves. This pilot study was conducted on six human subjects. The produced ultrasonic waves were collected from their anterior left arm under three experimental conditions, namely at rest, venous and arterial blood flow occlusions, for determination of hemoglobin absorption dependent phase change in tissue. The overall mean and standard deviation (STDEV) of phase angles for at rest condition are calculated as 1.43 ± 0.06 radians (rads). Higher phase angles are determined for diastolic and systolic occlusion pressures given by 1.69 ± 0.05 rads and 2.09 ± 0.06 rads, respectively. This work concluded that the feasibility of our PA system to monitor changes in tissue oxygen performance renders it a promising alternative for portable assessment and measurement of oxygen concentration within microcirculation environment.